2016
DOI: 10.1177/0049475516662804
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, serological and epidemiological observations after a suspected outbreak of plague in Nyimba, eastern Zambia

Abstract: Plague is a re-emerging zoonotic disease caused by the bacterium Yersinia pestis. The disease has caused periodic global devastation since the first outbreak in the 6th century. Two months after a suspected plague outbreak in Nyimba district, samples were collected from 94 livestock (goats and pigs), 25 rodents, 6 shrews and 33 fleas. Enzyme-linked immunosorbent assay (ELISA) and polymerase chain reaction (PCR) techniques were used to investigate the presence of Y. pestis, which showed that 16.0% (4/25) of rod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Sequences of strains isolated from these hosts were similar, indicating a multi-host zoonotic circulation and they demonstrated very close evolutionary relationships with Antiqua strains from the Democratic Republic of Congo and Kenya. In addition, serological studies conducted in the same area showed that 16.0% (4/25) of rodents, 16.7% (1/6) of shrews and 6.0% (5/83) of goats were positive for IgG antibodies against Fraction 1 antigen of Y. pestis, a result supporting the idea of active circulation of the bacterium in the geographic area [70]. Risk factors associated with human outbreaks in Zambia included heavy rains leading to a huge surge of rodents and fleas, hunting, unhygienic human habitats, preparation and consumption of rodents [71,72].…”
Section: Flea-borne Zoonotic Pathogensmentioning
confidence: 65%
“…Sequences of strains isolated from these hosts were similar, indicating a multi-host zoonotic circulation and they demonstrated very close evolutionary relationships with Antiqua strains from the Democratic Republic of Congo and Kenya. In addition, serological studies conducted in the same area showed that 16.0% (4/25) of rodents, 16.7% (1/6) of shrews and 6.0% (5/83) of goats were positive for IgG antibodies against Fraction 1 antigen of Y. pestis, a result supporting the idea of active circulation of the bacterium in the geographic area [70]. Risk factors associated with human outbreaks in Zambia included heavy rains leading to a huge surge of rodents and fleas, hunting, unhygienic human habitats, preparation and consumption of rodents [71,72].…”
Section: Flea-borne Zoonotic Pathogensmentioning
confidence: 65%
“…Traps were inspected the following morning and captured animals were taken to a nearby mobile laboratory for organ and flea collection. Trapping continued for three consecutive days in the same area as previously described elsewhere [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…These are Chama, Lundazi, Sinda and Nyimba [ 11 ]. However, in the past 15 years, the disease has occurred in the latter two districts, with the latest outbreak occurring in the Nyimba district in March 2015 [ 13 ]. No efforts have been made so far to identify the biotype or biovars of the bacterium in the area.…”
Section: Introductionmentioning
confidence: 99%
“…The study was conducted in the eastern Zambia, where plague has been reported in the recent past. In this area, four plague foci have been identified namely Tembwe in Chama District in 1917 and 1956, 2,3 Luembe in Nyimba District in 2015, 4 both are in northern and southern Luangwa valley. Others are Mukomba in Lundazi District in 1956 2 and Nyanje in Sinda District in 2001 and 2007.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Since then, a number of outbreaks of the disease have occurred in various parts of the country, the latest being in Nyimba District, southern part of Luangwa valley in March 2015, in which three fatal cases were recorded. 4 According to Low and Newman (1920), the spread of the disease from one village to another in Northern Luangwa valley was largely facilitated by sociocultural practices such as polygamy, where a man having more than one wife was shifting from one house or village to another and might have moved with infected fleas. Rodents hunting habits have also played a role in plague transmission.…”
Section: Introductionmentioning
confidence: 99%